Jungle animals - Hardyman, Robyn (2018)
"Information accompanies step-by-step instructions on how to make origami jungle animals. The text level and subject matter are intended for students in grades 3 through 8"--
Origami fun -- Monkey -- Frog -- Snake -- Tiger -- Macaw -- Elephant -- Chameleon -- Spider.
Includes bibliographical references and index.
Age 7-13.
Keywords: Origami -- Juvenile literature; Jungle animals in art -- Juvenile literature